DENSITY OF CUCUMBER SEED^PLANTS WHEN USING DROP IRRIGATION IN CONDITION OF EAST UKRAINE - A. V. Soldatenko (Овощи России)
The results of three-year study of density of cucumber seed-plants when using drop irrigation in condition and planting system 50+90 сm are shown. The optimal plant density for seed production purposes is 70 thousand plants on 1 hectare.